Quadravalvular Noninfectious Endocarditis - Peter P. Vlismas, MD; Jonas J. Heymann, MD; Charles C. Marboe, MD; Ulrich P. Jorde, MD; Daniel B. Sims, MD (JACC: Case Reports, 2019)
Nonbacterial thrombotic endocarditis is characterized by sterile thrombi on cardiac valves. This report describes the case of nonbacterial endocarditis without pathologic findings of fibrin or platelet deposition. Quadrivalvular endocarditis was found to be due to immunoglobulin M heavy chain deposition. This was a case of nonbacterial, nonthrombotic quadrivalvular endocarditis, which was termed noninfective endocarditis. (Level of Difficulty: Intermediate.)